Characteristics of lower extremity ulcers among patients treated at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, Bali - Puspita Sari, Luh Gede Melia; Suryawati, Nyoman (Universitas Gadjah Mada, 2023)
Lower extremity ulcers are one of the ulcers that are difficult to heal. This condition causes significant morbidity, mortality, costs, and reduces the quality of life. Epidemiological studies in Indonesia often focus on diabetic foot ulcers, so a general description of lower extremity ulcers is still lacking. This study aimed to determine the characteristics of lower extremity ulcers in outpatients at the Dermatology and Venereology Outpatient Polyclinic, Prof. Dr. I.G.N.G Ngoerah General Hospital, Denpasar, Bali. The data were taken retrospectively from medical records from January 2018 until December 2021. A total of 15 subjects were enrolled in this study. Among the subjects, 8 (53.3%) were male and 7 (46.6%) were female. The age group of 40 yo and over dominated this study (60%). The common ulcer predilection was on the cruris (42.1%) and the wound culture results were dominated by Staphylococcus aureus (40%). Comorbidities were found in 7 subjects (46.7%) and the majority was hypertension (42.8%). Several subjects also had additional diagnoses at the time of the visit, including Morbus Hansen (60%), deep vein thrombosis (10%), cellulitis (10%), pyoderma gangrenosum (10%), and systemic lupus erythematosus (10%). In conclusion, the most characteristics of lower extremity ulcer patients at Prof. Dr. I.G.N.G Ngoerah General Hospital are males, age group > 40 yr, with cruris as a predilection, and hypertension as the most common comorbid.